Assessing The Causal Relationship Between Payment Gateway Integration, Financial Literacy, and MSME Financial Performance - Sudaryanti, Dedeh Sri; Munawar, Andri Helmi; Yuniasih, Yuyun (BanKu: Jurnal Perbankan dan Keuangan, 2025)
Micro, small, and medium enterprises (MSMEs) play a crucial role in supporting Indonesia’s economic growth; however, their financial performance often remains limited due to low financial literacy and suboptimal technology adoption. This study aims to examine the influence of payment gateway integration and financial literacy on the financial performance of MSMEs by employing a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected from 100 active MSME owners through an online questionnaire and analyzed using SmartPLS 3.2.7. The findings reveal that both payment gateway usage and financial literacy have positive and significant effects on MSME financial performance. The R² value of 0.317 indicates that these variables jointly explain 31.7% of the variance in financial performance, with financial literacy showing a medium effect size and payment gateway a smaller yet significant effect. The study confirms that digital payment adoption improves transaction efficiency and security, while financial literacy enhances financial planning, budgeting, and risk management capabilities. Theoretically, this research extends the Technology Acceptance Model (TAM) and the Theory of Reasoned Action (TRA) by highlighting the complementary relationship between technological adoption and cognitive financial competence. Practically, the results suggest that MSME managers and policymakers should prioritize digital finance adoption and financial literacy training to strengthen financial resilience and sustainability. Overall, this study provides empirical evidence that combining digital innovation with financial education can significantly improve MSME performance and promote inclusive economic development in emerging economies.Keywords: Payment Gateway; Financial Literacy; Financial Performance; MSMEs; Fintech; Digital Transformation.